2022
DOI: 10.1186/s12886-022-02516-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of a presbyopia-correcting intraocular lens that combines extended depth-of-focus and bifocal profiles with a standard monofocal intraocular lens

Abstract: Background Recently, a new presbyopia-correcting intraocular lens (IOL) that combines extended depth-of-focus and bifocal profiles (ZFR00: Tecnis® Synergy®, Johnson & Johnson Vision, Santa Ana, CA, USA) has been established and several studies have been reported. We attempted to compare the performance with a standard IOL (ZCB00: Tecnis® monofocal, Johnson & Johnson Vision, Santa Ana, CA, USA) manufactured using the same material from the same company, which has been extensively used wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Not surprisingly, the objective optical quality of PL E, a standard monofocal IOL, was superior to Symbiose. This is a common finding in studies comparing monofocal IOL with presbyopia-correcting IOL 28 , 29 .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Not surprisingly, the objective optical quality of PL E, a standard monofocal IOL, was superior to Symbiose. This is a common finding in studies comparing monofocal IOL with presbyopia-correcting IOL 28 , 29 .…”
Section: Discussionmentioning
confidence: 63%
“…Similar to Symbiose, Tecnis Synergy (Johnson & Johnson Vision, Santa Ana, CA, USA) is a bifocal IOL combined with EDOF technology for a greater range of vision 29 . A comparison of the performance and characteristics of these two IOLs under the same conditions would be meaningful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several published studies have demonstrated that it performs well for distance, intermediate, and near vision at various ranges. [6][7][8][9][10][11][12][13] These studies have reported clinical outcomes from bilateral implantation of this lens in patients at near focal points of 33, 40, 66, and 80 cm. This author's experience with the Tecnis Symfony EDOF IOL (Johnson & Johson) 14 Institutional Review Board approval was obtained by the Houston Methodist Research Institute, Houston, TX.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Although near vision was much better than for a monofocal IOL and an EDOF lens made from a similar material, objective optical quality was reported to be slightly lower. 14,15 The Tecnis Symfony IOL is an EDOF lens that has been demonstrated to provide good intermediate and distance vision, with reported visual disturbances only slightly more severe than those experienced with a comparable monofocal IOL. 16 Halos were the most common visual disturbance associated with the lens.…”
mentioning
confidence: 99%